3-step analysis of public finances sustainability: the case of the European Union - António Afonso; Christophe Rault (European Central Bank (ECB), 2008)
We use a 3-step analysis to assess the sustainability of public finances in the EU27. Firstly, we perform the SURADF specific panel unit root test to investigate the meanreverting behaviour of general government expenditure and revenue ratios. Secondly, we apply the bootstrap panel cointegration techniques that account for the time series and cross-sectional dependencies of the regression error. Thirdly, we check for a structural long-run equation between general government expenditures and revenues via SUR analysis. While results imply that public finances were not unsustainable for the EU panel, fiscal sustainability is an issue in most countries, with a below unit estimated coefficient of expenditure in the cointegration relation with revenue as the dependent variable.
Keywords: C23; E62; H62; 330; EU; Fiscal sustainability; panel cointegration; Öffentliche Finanzen; Öffentlicher Haushalt; Nachhaltigkeit; Panel; Schätzung; EU-Staaten